Blood eosinophil count in the diagnosis of allergic‐like rhinitis with chronic rhinosinusitis. (26th October 2022) - Luo, Qiqi; Zhou, Siyi; Yuan, Bo; Feng, Zeli; Tan, Guolin; Liu, Honghui
Abstract: Background: Allergic rhinitis (AR) and nonallergic rhinitis (NAR) often are comorbid with chronic rhinosinusitis (CRS). Finding a convenient test that distinguishes these complex conditions is helpful for effective treatment. We aimed to analyse blood parameter differences between AR and NAR patients with/without CRS. Methods: Eight hundred thirteen patients, including AR and NAR with different conditions [CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP)] were analysed in this retrospective study. Patients with a nasal deviation alone were included as healthy controls (HC). Receiver operating characteristic analysis was used to assess the value of blood parameters for diagnosing AR or NAR with/without CRS. Results: Compared to nonallergic‐like rhinitis (HC, CRSwNP and CRSsNP), the blood eosinophil count was significantly increased in the allergic‐like rhinitis groups, except for NAR‐CRSsNP (AR, AR‐CRSwNP, AR‐CRSsNP, NAR and NAR‐CRSwNP). The NAR‐CRSsNP group had a higher level of eosinophils than the HC and CRSsNP groups. Among allergic‐like rhinitis patients, eosinophils were higher in allergic‐like rhinitis patients with CRSwNP (AR‐CRSwNP and NAR‐CRSwNP) than in allergic‐like rhinitis patients without CRSwNP (AR, AR‐CRSsNP, NAR and NAR‐CRSsNP). However, no difference in blood eosinophils was observed between AR and NAR. There was also no difference among nonallergic‐like rhinitis patients. Similar findings were found for the blood eosinophil proportion. Furthermore, the blood eosinophil count was a good predictor of allergic‐like rhinitis, especially allergic‐like rhinitis with CRSwNP. Conclusion: The blood eosinophil count and proportion may be good diagnostic predictors of allergic‐like rhinitis but cannot differentiate between AR and NAR. This indicator may be much better in predicting allergic‐like rhinitis with CRSwNP.